2022
DOI: 10.1038/s41598-022-13564-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of self-doped poly (5-nitro-2-orthanilic acid) as a scaling inhibitor to control the precipitation of CaCO3 and CaSO4 in solution

Abstract: Self-doped- and nitro-polyanilines have become a widely used strategy to optimize the electronic and vibratory spectra of polymeric building blocks in various applications. We report the synthesis of poly (5-nitro-2-orthanilic acid) by an aniline-initiated oxidative polymerization reaction. The polymer is characterized by spectroscopic techniques, elemental shapes, cyclic voltammetry, electrical conductivity, and microscopic and thermal measurements. The hydrophilic and hydrophobic nature of the supports provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Energy-dispersive X-ray spectroscopy (EDXS) was used to observe the morphologies of the polymers by scanning electron microscopy (SEM) (JEOL-JSMIT 200, Japan) and transmission electron microscopy (TEM) (JEOL-JTM-1400 plus, Japan) at the E-Microscope Unit, Faculty of Science, Alexandria University. The samples were sonicated in deionized water for 5 min, deposited onto carbon-coated copper mesh and allowed to air dry before examination [ 21 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy-dispersive X-ray spectroscopy (EDXS) was used to observe the morphologies of the polymers by scanning electron microscopy (SEM) (JEOL-JSMIT 200, Japan) and transmission electron microscopy (TEM) (JEOL-JTM-1400 plus, Japan) at the E-Microscope Unit, Faculty of Science, Alexandria University. The samples were sonicated in deionized water for 5 min, deposited onto carbon-coated copper mesh and allowed to air dry before examination [ 21 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…As part of an ongoing project directed to research the use of PANI and its functionalized analogues as multifunctional substrates for industrial application [ 21 24 ], we recently reported the chemical synthesis and characterization of poly(aniline-co-aniline-2,5-disulfonic acid) and its composite containing L-hexuronic acid (Fig. 1 ) and metallic Ag/SiO 2 nanoparticles as an efficient, new, thermally stable anionic polyelectrolyte to remove safranin dye from aqueous media [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…As part of an ongoing project directed to research in the field of using PANI and its functionalized analogues as multifunctional substrates for industrial application [21][22][23][24], we recently reported the chemical synthesis and characterization of poly(aniline-co-aniline-2,5disulfonic acid) and its composite containing L-hexuronic acid, Fig. 1, and metallic Ag/SiO2 nanoparticles, as an efficient, new, thermally stable anionic polyelectrolyte to remove safranin dye from aqueous media [25].…”
Section: Introductionmentioning
confidence: 99%
“…As a part of an ongoing project directed to new findings in the field of water treatment using functionalized polyanilines as highly promising candidates [18,19,20,21], we investigated the use of (aniline-co-aniline-2,5-disulfonic acid)/L-hexuronic acid/Ag@SiO 2 nanocomposites as a new highly anionic polyelectrolyte with an enhanced adsorptive effect for removing the cationic dye safranin. The incorporation of disulfonated units into the polymer chain should double the sulfonate groups on the backbone and produce regular molecular structure polymers with a higher sulfonation degree [22].…”
Section: Introductionmentioning
confidence: 99%